Helping Hands - Panayides, Angelos (My University, 2026)
This year’s festival highlights AI’s role in driving progress, enhancing creativity, and fostering global connections. Participants are invited to address critical contemporary issues and promote social change through innovative design. The theme encourages designers to explore the transformative impact of AI on our world, encompassing topics such as sustainability, global perspectives, innovation, societal transformation, cultural integration, and the synergy between creativity and technology. Designers are encouraged to select aspects that resonate with their interests and expertise and express their creative vision on how AI is shaping the future.